2017
DOI: 10.1016/j.physletb.2017.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional magnetic solutions in massive gravity with (non)linear field

Abstract: The Noble Prize in physics 2016 motivates one to study different aspects of topological properties and topological defects as their related objects. Considering the significant role of the topological defects (especially magnetic strings) in cosmology, here, we will investigate three dimensional horizonless magnetic solutions in the presence of two generalizations: massive gravity and nonlinear electromagnetic field. The effects of these two generalizations on properties of the solutions and their geometrical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 99 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…In addition, it was shown that this model is ghost free and stable [12]. The static black hole solutions and magnetic solutions in the presence of this model of massive gravity have been investigated in [13][14][15][16] and [17,18], respectively. Moreover, the thermodynamic properties and van der Waals like phase transition of black holes have been studied [14,[19][20][21][22].…”
Section: Jhep10(2019)207mentioning
confidence: 99%
“…In addition, it was shown that this model is ghost free and stable [12]. The static black hole solutions and magnetic solutions in the presence of this model of massive gravity have been investigated in [13][14][15][16] and [17,18], respectively. Moreover, the thermodynamic properties and van der Waals like phase transition of black holes have been studied [14,[19][20][21][22].…”
Section: Jhep10(2019)207mentioning
confidence: 99%
“…Magnetic solutions in the presence GB‐massive (non)linear electrodynamics were studied in ref. [], and it was shown that the massive terms significantly affect the singularity of deficit angle and their possible geometrical phase transitions. The existence of nonsingular universe in massive gravity's rainbow has been investigated and pointed out in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the generalizations of this massive theory to include higher derivative gravity [99], and gravity's rainbow extension [100] have been studied as well. In addition, black hole and magnetic solutions with (non)linear electrodynamics have been explored in the context of massive gravity [101,102].…”
Section: Introductionmentioning
confidence: 99%